2020
DOI: 10.3390/ijms21124521
|View full text |Cite
|
Sign up to set email alerts
|

Melatonin and Mesenchymal Stem Cells as a Key for Functional Integrity for Liver Cancer Treatment

Abstract: Hepatocellular carcinoma (HCC) is the most common hepatobiliary malignancy with limited therapeutic options. On the other hand, melatonin is an indoleamine that modulates a variety of potential therapeutic effects. In addition to its important role in the regulation of sleep–wake rhythms, several previous studies linked the biologic effects of melatonin to various substantial endocrine, neural, immune and antioxidant functions, among others. Furthermore, the effects of melatonin could be influenced through rec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 168 publications
(228 reference statements)
2
7
0
Order By: Relevance
“…Therefore, it is highly suggestive that the restoration of cardiac glucose utilization revealed in this study was a result of a melatonin‐induced attenuation of ventricular hypertrophy that was observed in a prior study 19 . Consistent with our findings, several previous studies also found that melatonin suppressed glycolysis in various types of cancer cells, leading to a delay in tumor growth and increased chemosensitivity 42–46 . For this reason, it is possible that melatonin itself can protect against doxorubicin‐induced heart failure by limiting the utilization of cardiac glucose.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Therefore, it is highly suggestive that the restoration of cardiac glucose utilization revealed in this study was a result of a melatonin‐induced attenuation of ventricular hypertrophy that was observed in a prior study 19 . Consistent with our findings, several previous studies also found that melatonin suppressed glycolysis in various types of cancer cells, leading to a delay in tumor growth and increased chemosensitivity 42–46 . For this reason, it is possible that melatonin itself can protect against doxorubicin‐induced heart failure by limiting the utilization of cardiac glucose.…”
Section: Discussionsupporting
confidence: 91%
“…19 Consistent with our findings, several previous studies also found that melatonin suppressed glycolysis in various types of cancer cells, leading to a delay in tumor growth and increased chemosensitivity. [42][43][44][45][46] For this reason, it is possible that melatonin itself can protect against doxorubicin-induced heart failure by limiting the utilization of cardiac glucose. To support this statement, a future study using a rat model pretreated with melatonin is needed.…”
Section: Doxorubicin Increased Mitochondrial Oxidative Stress In Embr...mentioning
confidence: 99%
“…Limits of interpretation result from approaches in which CSCs are subjected to combined treatments with melatonin and a cytostatic agent. Another type of combination was applied in hepatocellular carcinoma, in which MSCs were tested for their therapeutic potential in the presence of melatonin [234]. In this case, an increase of apoptosis was reported, something that would be in accordance with experience from applications of melatonin alone in tumor cells.…”
Section: Some Aspects Concerning Cancer Stem Cellssupporting
confidence: 73%
“…167 Several studies reported that MLT plays significant role in various functions such as endocrine, neural, immune and antioxidant functions both receptor dependent and independent manner. 168 MLT inhibits HepG2 and Hep3B proliferation and cell cycle progression via affecting the cell cycle-associated proteins. MLT potentiates cisplatin-induced apoptosis associated with upregulated caspase-3 and poly ADP-ribose polymerase (PARP) cleavage, as well as Bcl-2 expression.…”
Section: Role and Therapeutic Potential Of Mlt In Liver Cancermentioning
confidence: 99%